Analysis of the need of the organizations of the popular and solidarity economy of zone 1. - García Ibarra, Verónica Jeaneth; Chávez Rosero, Jairo Ricardo (SATHIRI, 2020)
This research is a step in identifying the current state of the organizations of the People’s and Solidarity Economy together with the problems and needs arising. The economic situation oforganizations was analyzed with historical data, as well as their future prospects, identified the problems that most affect the popular and solidarity sector. For which quantitative, descriptive enforque was applied, the collection of information was done through the survey by applying the non-probabilistic method for convenience and information was collected from 10 organizations in the Carchi, 14 in Esmeraldas, 17 in Imbabura and 26 in Sucumbíos, by simple random sampling focusing on the organizations of the main sectors in number of registered organizations:agricultural, textile, food, cleaning and transport. From the study, information has been obtained that will serve as an input for taking actions with the aim of reducing the impact of the problem and needs. The main conclusions that were obtained are: a gradual reduction of the economy over the past five years, the EPS Organizations need technical training to enable them to technify their processes and among the pressing needs is the lack of liquidity. The information is derived is part of the Ecuador-Colombia. Border Development research project. Analysis period 2017- 2019 as part of the Associativity component.
Keywords: Economy; Popular and Solidarity; problems; needs